2016
DOI: 10.3109/13880209.2016.1168853
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic activity of total triterpenes isolated fromPoria cocosis mediated by suppression of aspartic and glutamic acids in the brain

Abstract: Context: Triterpenes from Poria cocos Wolf (Polyporaceae) have been used to treat various diseases in traditional Chinese medicine. However, the antiepileptic effects and mechanism are not fully understood. Objective: The objective of this study is to investigate the antiepileptic properties of total triterpenes (TTP) from the whole P. cocos. Materials and methods: The ethanol extract TTP was identified by HPLC fingerprint analysis. Male ICR mice were gavaged (i.g.) with TTP (5, 20, 80 or 160 mg/kg) or referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The B-ring in flavonoids, which is rich in hydroxyl groups, reacts with superoxide [49]. Some studies have shown that some terpenes regulate the glutamate decarboxylase expression and aspartic and glutamic acid levels in the brain [50] and that the GABA agonist capacity of some flavonoids is related to hydroxyl positions [51]. These different mechanisms could explain the effects of the main metabolites in acetonic and methanolic extracts of H. inuloides in attenuating seizures in epileptic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The B-ring in flavonoids, which is rich in hydroxyl groups, reacts with superoxide [49]. Some studies have shown that some terpenes regulate the glutamate decarboxylase expression and aspartic and glutamic acid levels in the brain [50] and that the GABA agonist capacity of some flavonoids is related to hydroxyl positions [51]. These different mechanisms could explain the effects of the main metabolites in acetonic and methanolic extracts of H. inuloides in attenuating seizures in epileptic rats.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6,7]. Modern studies have shown that triterpenoids in W. cocos have diverse pharmacological effects, such as anti-epilepsy, anti-apoptosis, diuresis, cytotoxicity, liver protection, anti-leukemia, anti-inflammatory, and so on [8,9,10,11,12,13,14,15,16]. Therefore, W. cocos has a wide and important role in future medical application.…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of medicine food homologous fungus, on the one hand, it is used to treat diseases, such as edema, insomnia, spleen deficiency, and vomiting 2 . Modern researches showed that the main active compositions were polysaccharides and triterpenes in W. cocos , which possessed a wide range of pharmacological activities including anti‐tumour, anti‐inflammatory, anti‐oxidant, anti‐bacterial, hepatoprotective, etc 3–8 . On the other hand, it is used as a food material, as early as the Qing Dynasty, such as Poria cakes.…”
Section: Introductionmentioning
confidence: 99%